Factors affecting postnatal weight gain of very low birth weight babies during NICU stay in a tertiary care centre in Southern India: an observational study - Nanjappan, Vidhya Shankari; K., Senthil Kumar; Duraisamy, Senguttuvan (International Journal of Contemporary Pediatrics, 2024)
Background: The survival of very low birth weight babies has significantly improved in recent years. Postnatal growth has an impact on neurodevelopment and hence identifying the risk factors that curb growth is crucial. Methods: We did a retrospective cohort study over 3 months in our NICU studying 40 very low birth weight babies. Our objective was to observe the time taken to regain birth weight and study the risk factors affecting postnatal weight gain. Results: Among the 40 babies studied, 22 babies had significant delay in regaining birth weight. Risk factors such as birth weight, birth asphyxia, parenteral nutrition, respiratory distress syndrome, surfactant requirement, patent ductus arteriosus, necrotizing enterocolitis, sepsis, hyperbilirubinemia, anemia had statistically significant association with delay in regaining birth weight. Conclusions: Many studies have established a linear correlation between postnatal growth velocity and neurodevelopmental outcome. Ascertaining and managing the factors affecting weight gain in very low birth weight babies is essential and challenging part and anticipating the risk factors in advance helps us to achieve desirable weight gain in these babies.